Optimizing the Number of Child Deaths Averted with Mass Azithromycin Distribution - Oldenburg, Catherine E. (Am J Trop Med Hyg, 2020)
Biannual mass azithromycin distribution to children younger than 5 years has been shown to reduce all-cause mortality in sub-Saharan Africa. Antibiotic-sparing approaches to azithromycin distribution, such as targeting to younger children who are at higher risk of mortality, are being considered by policymakers. We evaluated the absolute number of deaths averted in the Macrolides Oraux pour Réduire le Décès avec un Oeil sur la Résistance study in three age-groups: 1–5 months, 1–11 months, and 1–59 months. The number of deaths averted decreased from 729 (95% CI 492 to 966) in children aged 1–59 months to 297 (95% CI 168 to 427) and 126 (95% CI 43 to 209) in the 1- to 11-month and 1- to 5-month groups, respectively. Limiting antibiotic treatment to a subgroup of higher risk children may result in fewer deaths averted compared with treating all preschool children.